Percepción de la imagen corporal en la satisfacción sexual en adultos jóvenes - Valarezo Armijos, Karla María (2024)
Body image has been evolving unprecedentedly in recent years a significant concern is presented in young adults because human beings develop at a biopsychosocial level; their beliefs, thoughts, and interactions transform, and for this particular reason at this period, they build an identity influenced by society, culture, media, and social networks, being a risk factor in case they do not fit the established prototypes, having a considerable influence on the daily life of people, even in the sexual sphere, which we circumscribed by the establishment of prototypes, media, and social networks, being a risk factor in case of not fitting with the established prototypes, having an utmost influence on the daily life of people, even in the sexual sphere, which is circumscribed by a historical and cultural context and therefore, determined by customs, traditions, and values and in turn, has an impact on these; therefore, the present study aims to describe the scientific evidence of the perception of body image in the sexual satisfaction of young adults in Latin America, we conducted the research through a literature search and had a quantitative, descriptive, and cross-sectional approach, non-experimental design, and correlational scope. The selected sample consisted of 13 scientific articles from Latin American countries, sampled by non-probabilistic sampling using the PRISMA method. Finally, according to the results, we concluded that most young adults presented body dissatisfaction concerning an adequate body image, and the countries where there was a higher prevalence were Colombia, Mexico, and Costa Rica, and concerning sexual satisfaction showed a high level compared to the low level, presenting a higher prevalence in countries such as Chile, Bolivia, and Mexico. In addition, we designed an informative guide that addressed issues related to a healthy body image and provided tools to promote a perception of adequate body image in sexual satisfaction